Arabidopsis Relatives of the Human Lysine-Specific Demethylase1 Repress the Expression of FWA and FLOWERING LOCUS C and Thus Promote the Floral Transition - Jiang, Danhua (American Society of Plant Biologists, 2007)
The timing of the developmental transition to flowering is critical to reproductive success in plants. Here, we show that Arabidopsis thaliana homologs of human Lysine-Specific Demethylase1 (LSD1; a histone H3-Lys 4 demethylase) reduce the levels of histone H3-Lys 4 methylation in chromatin of the floral repressor FLOWERING LOCUS C (FLC) and the sporophytically silenced floral repressor FWA. Two of the homologs, LSD1-LIKE1 (LDL1) and LSD1-LIKE2 (LDL2), act in partial redundancy with FLOWERING LOCUS D (FLD; an additional homolog of LSD1) to repress FLC expression. However, LDL1 and LDL2 appear to act independently of FLD in the silencing of FWA, indicating that there is target gene specialization within this histone demethylase family. Loss of function of LDL1 and LDL2 affects DNA methylation on FWA, whereas FLC repression does not appear to involve DNA methylation; thus, members of the LDL family can participate in a range of silencing mechanisms.